An overview for demographic and environmental issues in sustainable agriculture in sub-Saharan Africa - Mohamed-Saleem, M.A.; Fitzhugh, H.A. (International Livestock Centre for Africa, 1995)
Ever-increasing human population and urbanisation are intensifying the demand for agricultural commodities in sub-Saharan Africa (SSA). As a result, the traditional balance between people, their habitat and socio-economic systems is fast disappearing. Excessive deforestation, land clearing and cultivation are occurring in an attempt to meet rising food demands. Land degradation and pollution threaten sustainable increases in agricultural productivity and endanger the survival of present and future generations. Changes in agricultural production are needed soon in sub-Saharan Africa to avert large-sacle human suffering. Despite the rapidly growing population and enormous production constraints, SSA can become agriculturally self sufficent. This will require imaginative food production techniques and management approaches that protect the environment at unprecedented scales. These changes can only be realised through changes in political will and national attitudes.